PERAN TENAGA ADMINISTRASI DALAM MENINGKATKAN AKSESIBILITAS PENGUATAN TRANSFIGURASI KURIKULUM DI SEKOLAH DASAR - Yoni Napizah; Ahmad Hariandi; Andi Gusmaulia Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the role of administrative staff in enhancing the accessibility of curriculum transformation reinforcement at SDN 34/I Teratai during the odd semester of the 2024/2025 academic year. This research employs a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation involving administrative staff as the primary source, along with school principals and teachers as supporting informants. Data validity was tested through triangulation of techniques and sources. The findings indicate that administrative staff play a crucial role in seven key areas: (1) Personnel Administration, managing teacher data and supporting adaptation to curriculum policies; (2) Financial Administration, ensuring budget transparency and distributing BOS funds; (3) Facilities Administration, managing educational infrastructure to support curriculum implementation; (4) Public Relations Administration, facilitating communication between the school and external stakeholders; (5) Correspondence and Archival Administration, distributing curriculum documents and academic policies; (6) Student Administration, managing student data and development programs; and (7) Curriculum Administration, assisting in the preparation and distribution of curriculum documents. This study concludes that administrative staff play a vital role in facilitating curriculum transformation in elementary schools. Optimizing digital-based administration and enhancing the competence of administrative staff are strategic steps to improve educational accessibility, making it more inclusive and adaptable to modern developments.